An integrated approach to investigate the relationship of coupling coordination between social economy and water environment on urban scale - A case study of Kunming. (15th March 2019) - Cui, Dan; Chen, Xin; Xue, Yinglan; Li, Rui; Zeng, Weihua
Abstract: With a rapid economic growth and social development in China, the associated problems of water pollution and shortage of water resources would limit the sustainable and coordinated development of socioeconomic and water environmental systems of urban cities. To investigate the relationship of coupling coordination between social economy and water environment on urban scale, we introduced an integrated approach that enables the dynamic evaluation of coupling coordination degree (CCD), which consists of a system dynamics model and a coupling coordination degree model; and applied it to a case study in Kunming in 2016–2025. The business-as-usual (BAU) scenario and five alternative regulating scenarios are simulated to evaluate the effectiveness exerted by various socioeconomic development patterns and water protection efforts in improving CCD. We found that the improvement of CCD could attribute to both the sufficient water protection efforts and the maintaining sustainable speed and scale of socioeconomic development patterns. Under BAU scenario, Kunming would maintain the current state of barely balanced development with CCD at 0.5–0.8, predominantly due to substantial water consumption and pollution. Through the comparison of dynamic evolutions of system indicators and CCD under five alternative regulating scenarios, it is realistic for Kunming to plan its future development in accordance to M-H scenario (Medium-speed socioeconomic development pattern; High-intensity water protection effort). Following this scenario, Kunming's CCD would conform to a steadily increasing trend in 2016–2025 and remain above 0.8 in 2022–2025, tracing a shift in the development stage of that coupling coordination from "barely balanced development" to "highly balanced development" despite the difficulty to cut NH3 -N emission significantly. The effective and feasible regulatory measures such as reducing productive or domestic water pollutants and consumptions; improving collection and reuse rates of wastewater, should be prioritized when adjusting coordination development during decision-making. Graphical abstract: Image 1 Highlights: We studied coupling coordination of social economy-water environment of a city system. An integrated model is developed and applied to test regulating scenarios in Kunming. Kunming would benefit under moderate development-high water protection conditions. Regulatory measures could improve coupling coordination degree in decision-making.